INVESTIGATION OF DIAMOND LIKE CARBON COATING FOR FRICTION STIR WELDING TOOL - MOHD AMIR NOR RABI, MOHD AMIRUL AFIQ (2018)
Friction Stir Welding (FSW) is a substitute to the conventional welding methods to join metal matrix composites that demonstrates many advantages such as higher strength and joints with low porosity. Having said that, it is rather limited in application where it can only join low-strength materials such as aluminum metal composites. For higher-strength materials such as stainless steel, the current tool, PCBN tool experiences harsh wear due to the contact between the tool and the stainless-steel workpiece. Thus, the objectives of this project are to study the microstructure of the tungsten carbide diamond like carbon tool, as well as to investigate the wear rate of the tungsten carbide diamond like carbon welding tool by measurement and calculation of the percentage of mass reduction after each weld. Each initial and final mass of the tool were noted to calculate the tool wear rate. Some mechanical testing was conducted to assess the surface properties of the coated tool, such as Scanning Electron Microscope (SEM), Scratch Test and Microhardness Test. The hardness of each sheet of workpiece obtained proved that it categorized as 300-series austenitic stainless-steel category. The Critical Scratch Load and Hardness of the FSW tool were found to be lower than each of their expected range. From the results of SEM, the FSW tool chemical composition and layer morphology were determined with the right side and bottom side of the tool being examined. The right-side surface of the tool appeared very even and exhibited purely elements for tungsten carbide and diamond like carbon coating, with chromium and tungsten having the highest content; 44.7% and 22.2% respectively, while carbon and cobalt were the elements with lowest content. For the bottom side, the surface appeared heavily deformed and damaged. It was then discovered that it was due to the workpiece metal depositing on the tool, rather than the tool experiencing severe wear, with stainless steel elements such as iron, nickel and silicon appearing in the chemical composition of the tool. This proved that the coating-substrate system of the tool was strong and did not experience severe wear. Thus, it is proven that the tungsten carbide tool coated with diamond like carbon is capable of welding the stainless-steel composite plates together and is adept at reducing the tool wear rate.